Characterization of the Fecal Microbiome in Dogs Receiving Medical Management for Congenital Portosystemic Shunts - Squire, Nathan; Lux, Cassie; Tolbert, Katie; Lidbury, Jonathan; Sun, Xiaocun; Suchodolski, Jan S. (Frontiers in Veterinary Science, 2022)
Background The GI microbiome has not been characterized in dogs being medically managed for congenital portosystemic shunts (CPSS). Objectives To characterize the fecal microbiome in a population of dogs being medically managed for CPSS. Animals 27 client-owned dogs. Methods Prospective cohort study enrollment of fecal samples was performed with follow-up data collected retrospectively. The overall fecal dysbiosis index (DI) and individual bacterial abundances were determined using real-time qPCR. Medical management, clinical findings, clinicopathologic, and outcome variables were collected, and logistic regression analyses were performed to evaluate associations between these variables and overall DI and bacterial abundances. Numerical variables were evaluated with general linear models for normality and equal variance using Shapiro-Wilk test and Levene's test, respectively. Results All dogs were administered a hepatic diet and lactulose, while antibiotics were used in 22 (81.5%) and acid suppressants in 7 (25.9%). Seventeen dogs (63.0%) had a DI >2. The median DI in this population was 3.02 (range 4.23–8.42), and the median DI in dogs receiving and not receiving antibiotics was 4.3 (range −4.23–8.42) and 1.52 (range −1.62–5.43), respectively. No significant association between any of the analyzed variables and the DI was identified. There was a significant association between the use of metronidazole and a larger abundance of E. coli (p = 0.024). Conclusions and Clinical Importance Dysbiosis appears to be common in dogs that are being medically managed for CPSS, though the clinical significance remains unclear.